Air-Based Coaxial Dielectric Barrier Discharge Plasma Source for Pseudomonas aeruginosa Biofilm Eradication - Soler Arango, Juliana (2017)
Biofilms cause biofouling, pipe plugging, prostheses colonization, disease, and nosocomial infections. Bacterial biofilms are more resilient to sterilization methods than planktonic bacteria; therefore, better control methods are required. The use of gas discharge plasmas is an appropriate alternative because plasmas contain a mixture of reactive agents that are well known for bacterial decontamination. This study assesses culture medium-abiotic surface combinations leading to robust biofilms and tests an air-based coaxial dielectric barrier discharge (DBD) plasma source on Pseudomonas aeruginosa biofilms grown in continuous culture under those selected conditions. Biofilms were eradicated after a 15-min plasma treatment, resulting in a CFU/mL decrease of 5.6 log10 units. CFU/mL decreases of 1.6 and 2.7 log10 units were achieved after a 3-min plasma exposure to ambient and moistened air plasma, respectively, although viability assays showed that some cells were alive. Moistened-air plasma resulted in a faster biofilm inactivation, with decimal reduction times of 1.14 and 4.36 min. The coaxial DBD air-based plasma source presented here is effective for Pseudomonas biofilm inactivation, affordable because it does not rely on expensive gases, and easy to handle for indirect surface treatment. To the best of our knowledge, the search for the best combination medium surface leading to robust biofilms before plasma treatment has not been previously assessed.